Identification of resilience factors in rail engineering work - Ferreira, Pedro (2013)
This paper discusses an ongoing project that aims at improving the potential for resilience of a system responsible for the planning of rail engineering work delivery. It focuses on the use of a human factors based approach as a way to achieve this end. In particular, the paper discusses the initial data collected by means of interviews and how this process gave way to a two fold goal: Understanding how the planning process works in reality and identifying any critical aspects of the system from a Resilience Engineering perspective. Given the nature of the process under study, information flows and communication issues have been given particular attention throughout the data collection and analysis stages. Initial data confirms that the planning process is greatly reliant on the capability of people using their knowledge and skills to communicate in a dynamic informational environment. Finally, the added value of the interviews is discussed from a human factors perspective and as a mean towards the aim of better understanding resilience in rail engineering planning.